(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
The primary purpose of rail pads is to prevent cracking in concrete connections, which is assumed to be caused by the passing train's impact and vibration generated by movement from its wheels. To ensure the usage of rail pads is reliable and safe, failure and fatigue life prediction need to be done. However, analyzing fatigue conditions using the experimental method is time-consuming and costly. Thus, this work aims to develop a finite element model for analyzing the fatigue and life cycle of the rail pads. By using the simulation method, the time and cost of analyzing the process can be reduced. The rail fastening system model comprises a steel rail, rail pad, and concrete sleeper. The Mooney-Rivlin model was used to develop the rail pad, and the isotropic elasticity model was used for the steel rail and concrete sleeper. Using the modified Goodman theory, this study was able to estimate the fatigue life of the rail pad in terms of the number of cycles for a range of compressive forces and toe load. The findings show that a toe load at 18 kN shows more life cycle compared to a higher toe load of 35 kN with more than 50% difference. The life cycle also reduces as the load applies increases. This concludes that the fatigue life of the rail pad is greatly dependent on the toe load condition and compressive load. The rail pad is less durable under greater compressive load circumstances.